Analisis Indeks Massa Tubuh (IMT) dan Daya Tahan Pada Atlet SSB Persid Sidoluhur Godean Sleman - Hafizhudin, Kholis Anang; Iwandana, Dody Tri (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2024)
This research aims to determine the Body Mass Index (BMI) and endurance system of SSB Persid Sidoluhur Godean Sleman Athlete. The research method uses a quantitative approach, the research was carried out by SSB Persid Sidoluhur Godean Sleman with a total of 15 respondents aged 14-15 years using an instrument in the form of a beep test form and then calculations were carried out to obtain the average, median, mode and frequency of the Mass Index. Body (BMI) and beep test form. The research results showed that there were 13 respondents with a normal BMI category and two respondents with a fat BMI category. Meanwhile, the results of measuring the endurance of respondents obtained an average beep test level value of 13.73 with a return number of 6.47, which shows that the average athlete has good endurance in order to increase the training portion. The research conclusions show that the majority of SSB Persid Sidoluhur Godean Sleman athletes have a normal BMI category and a good level of endurance. However, there is a need to monitor athletes with a fat BMI category and increase training that focuses on endurance. It is also important to provide an understanding of balanced diet and nutrition and involve coaches and support staff in the development of a comprehensive training program. In this way, it is hoped that athletes can achieve better achievements in the sport of football. Keywords: Beep Test, Endurance, Body Mass Index (BMI).